High power mechanical energy harvester based on exfoliated black phosphorous–polymer composite and its multiple applications. Issue 8 (3rd July 2019) - Singh, Sachin Kumar; Muduli, Subas; Dhakras, Dipti; Pandey, Richa; Babar, Rohit; Singh, Ankur; Kabra, Dinesh; Kabir, Mukul; Boomishankar, Ramamoorthy; Ogale, Satishchandra
Abstract : A uniformly dense dispersion of few layer BP (FLBP) nanosheets in PDMS (polydimethylsiloxane) matrix is shown to exhibit a remarkably strong mechanical energy harvesting effect with highest peak-to-peak voltage output of about 350 V. Abstract : Black phosophorous (BP) and its 2D analogue phosphorene are endowed with several striking properties due to their unique puckered structure. One attribute that can potentially attract multiple applications of interest, and yet not fully addressed, is their mechano-electric response. Herein, we demonstrate the utility of an uniformly dense dispersion of few layer BP (FLBP) nanosheets in PDMS (polydimethylsiloxane) matrix, with a high 2D-dielectric interface density, exhibiting a remarkably strong mechanical energy harvesting effect. A highest peak-to-peak voltage output of about 350 V is achieved with a maximum current density of 12.8 mA m −2 under an applied impact force of 40 N, at a frequency range of 20–25 Hz. This corresponds to a volume power density of 2 kW m −3 with active material (BP) contribution of 0.35 W g −1 . Notably, the 2D BP nanosheets themselves are found to exhibit a fairly high piezoelectric coefficient of ∼20 pm V −1 as revealed by the piezoresponse force microscopy (PFM). First principles DFT calculations suggest the existence of strain-induced polarization in the BP layers via deformation-induced redistribution of intra-layer electron charge density. Based on the experimental and theoretical findings, we propose a synergistic multi-polarization mechanism that contributes to the strength of the observed energy harvesting effect. We also present three interesting practical modes of energy harvesting by subjecting them to the rapid flow of water, bicycle wheel motion and tapping induced LED lighting.